ChemInform Abstract: Codoping in SnTe: Enhancement of Thermoelectric Performance Through Synergy of Resonance Levels and Band Convergence. Issue 32 (August 2015) - Tan, Gangjian; Shi, Fengyuan; Hao, Shiqiang; Chi, Hang; Zhao, Li‐Dong; Uher, Ctirad; Wolverton, Chris; Dravid, Vinayak P.; Kanatzidis, Mercouri G.
Abstract The thermoelectric performance of p‐type SnTe is enhanced over a broad temperature range with a peak ZT (figure of merit) value of ≈1.4 at 923 K via In/Cd co‐doping and CdS nanostructuring.